Evaluation of Evaporative Cooling Structure (ECS) and Artificially Aerated Onion Structure (AAOS) for Storage of Fresh Red Onion. - Adu, E. A.; Bamishaiye, E. I.; Ibrahim, B.; Jude, J.; Kamaldeen, O. S.; Isiaka, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Storage of onion usually by cooling has been problematic due to poor electricity supply. Thus, this study assessed the effectiveness of artificially aerated onion structure (AAOS) and evaporative cooling structure (ECS) for the storage of fresh red onion. A total of 4650kg of red onion was stored for 7 months (March to October) and was monitored monthly to observe physiological and biochemical changes using AAOC and other standard methods. Data collected were subjected to descriptive statistics and t-test at significant difference of P<0.05 using SPSS. Increase in the percentage weight loss of the stored onion was observed as relative humidity increased especially when the relative humidity surpassed 50%. ECS had 27.03% weight loss recorded in May (2nd month of storage) while AAOS had 11.1% weight loss in July (Fourth month of storage). At the end of the experiment the average weight loss was 65.76%, 72.00%, and 76.12% for AAOS, Conventional method and ECS respectively. There was an increasing trend in the proteins, carbohydrates and oil contents of onion in AAOS and were significantly (p < 0.05) higher than the increase in conventional storage method and ECS. Declining trend was observed in ascorbic acids (AA) contents in the stored onions in all treatments leaving more retention (10.4% AA and 5.48% AA), in AAOS and conventional storage method respectively more than in ECS. Total polyphenolic contents increased from an initial 5.10±0.02 to 12.08±0.00, 9.95±1.03 and 8.97±1.03 GAE (mg/g) fresh weight in AAOS, conventional storage method and ECS respectively.